Fluid retention and utility of practical hydration markers to detect three levels of recovery fluid intake in male runners - Stevenson Wilcoxson, M. C.; Johnson, S. L.; Pribyslavska, V.; Green, J. M.; O`Neal, E. K. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Runners are unlikely to consume fluid during training bouts increasing the importance of recovery rehydration efforts. This study assessed urine specific gravity (USG) responses following runs in the heat with different recovery fluid intake volumes. Thirteen male runners completed 3 evening running sessions resulting in approximately 2,200 +/- 300 ml of sweat loss (3.1 +/- 0.4% body mass) followed by a standardized dinner and breakfast. Beverage fluid intake (pre/postbreakfast) equaled 1,565/2,093 ml (low; L), 2,065/2,593 ml (moderate; M) and 2,565/3,356 mL (high; H). Voids were collected in separate containers. Increased urine output resulted in no differences (p > .05) in absolute mean fluid retention for waking or first postbreakfast voids. Night void averages excluding the first void postrun (1.025 +/- 0.008; 1.013 +/- 08; 1.006 +/- 0.003), first morning (1.024 +/- 0.004; 1.015 +/- 0.005; 1.014 +/- 0.005), and postbreakfast (1.022 +/- 0.007; 1.014 +/- 0.007; 1.008 +/- 0.003) USG were higher (p < .05) for L versus M and H respectively and more clearly differentiated fluid intake volume between L and M than color or thirst sensation. Waking (r = -0.66) and postbreakfast (r = -0.71) USG were both significantly correlated (p < .001) with fluid replacement percentage, but not absolute fluid retention. Fluid intake M was reported as most similar to normal consumption (5.6 +/- 1.0 on 0-10 scale) after breakfast and equaled 122 +/- 16% of sweat losses. Retention data suggests consumption above this level is not warranted or actually practiced by most runners drinking ad libitum, but that periodic prerun USG assessment may be useful for coaches to detect runners that habitually consume low levels of fluids between training bouts in warm seasons.